β1-Integrin plays a major role in resveratrol-mediated anti-invasion effects in the CRC microenvironment - Brockmueller, Aranka; Mueller, Anna-Lena; Shayan, Parviz; Shakibaei, Mehdi (Frontiers in Pharmacology, 2022)
Background: Tumor microenvironment (TME) is one of the most important factors in tumor aggressiveness, with an active exchange between tumor and other TME-associated cells that promotes metastasis. The tumor-inhibitory effect of resveratrol on colorectal cancer (CRC) cells has been frequently reported. However, whether resveratrol can specifically suppress TME-induced CRC invasion via β1-integrin receptors has not been fully elucidated yet. Methods: Two CRC cell lines (HCT116, RKO) were cultured in multicellular, pro-inflammatory 3D-alginate TME cultures (containing fibroblasts, T-lymphocytes) to investigate the role of β1-integrin receptors in the anti-invasive and anti-metastatic effect of resveratrol by antisense oligonucleotides (ASO). Results: Our results show that resveratrol dose-dependently suppressed the formation of local adhesion sites on cytoplasmic membranes, the expression of E-cadherin associated with the phenotype change of CRC cells, and their invasion. Moreover, resveratrol blocked TME-induced phosphorylation and nuclear translocation of p65-NF-kB, which was associated with changes in the expression pattern of epithelial-mesenchymal-transition-related biomarkers (slug, vimentin, E-cadherin), metastasis-related factors (CXCR4, MMP-9, FAK), and apoptosis (caspase-3). Finally, transient transfection of β1-integrin, in contrast to knockdown of NF-kB, abrogated most anti-invasive, anti-metastatic effects as well as downstream signaling of resveratrol, resulting in a concomitant increase in CRC cell invasion, indicating a central role of β1-integrin receptors in the anti-invasive function of resveratrol. Conclusion: These results demonstrate for the first time that silencing β1-integrins may suppress, at least in part the inhibitory effects of resveratrol on invasion and migration of CRC cells, underscoring the crucial homeostatic role of β1-integrin receptors.